Kontrasty . Kontrasty . Contrasts . Контрасты - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The political course in Russia and arrangement of political forces; interview with the politician Aleksandr Tikhonov; survey of the history of the State Duma of the Russian Empire; forthcoming elections. Featured in the program: Gaidar, Egor Timurovich (First Deputy Head of the Council of Ministers of Russia); Borovoi, Konstantin Natanovich (Politician); IAvlinskii, Grigorii Alekseevich (Politician) Contributors: Svanidze, Nikolai (Anchor) Политическом курсе России и расстановка политических сил; интервью с политиком Александром Тихоновым; обзор истории Государственной думы Российской Империи; предстоящие выборы. В программе участвуют: Гайдар, Егор Тимурович (Первый заместитель председателя Совета Министров России); Боровой, Константин Натанович (Политик); Явлинский, Григорий Алексеевич (Политик) Создатели: Сванидзе, Николай (Ведущий/Ведущая)